New markets and new jobs - Spiezia, Vincent (Paris, 2016)
"This report provides new evidence on the effects of digital technologies on labour demand and discusses key policies to foster employment in the digital economy. The digital economy has the potential to enhance productivity, income and social well-being. It is creating job opportunities in new markets and increasing employment in some existing occupations. As digital technologies enable the production of more goods and services with less labour, they also expose some workers to the risk of unemployment or lower wages. They also enable changes in the organisation of work, with implications for the capability of existing policies and programmes to ensure labour market inclusion, job quality and skills development. The report discusses policies to foster growth and employment in new economic activities enabled by digital technologies, to accompany workers along the transition to new jobs, and to help ensure job quality in the digital economy."